Waste management literacy in Indonesian secondary schools: Assessing knowledge, attitudes, and behavior - Nisa, Khaerun; Aflahah, St; Aldeia, AM Saifullah; Witteveen, Loes; Lie, Rico (Jurnal Cakrawala Pendidikan, 2025)
This study explores waste management literacy among secondary school communities in Tangerang City, Indonesia, using the Knowledge, Attitude, Behavior (KAB) model within the 3R (Reduce, Reuse, Recycle) framework. Employing a mixed-methods sequential explanatory design, the research integrates quantitative data from 357 participants including principals, teachers, staff, and students from seven schools near the Rawa Kucing Landfill, with qualitative insights from follow up interviews. This study was applied to multiple regression and correlation analyses to evaluate relationships between knowledge, attitude, and behavior. Results show that while knowledge positively influences behavior, attitude unexpectedly correlates negatively, revealing an attitude-behavior gap. Although respondents generally hold positive attitudes toward waste management, these attitudes do not consistently translate into active engagement. The study’s qualitative phase uses interviews to identify barriers contributing to this gap, uncovering individual, social, and structural obstacles such as inadequate facilities and established waste practices that hinder effective waste management. Advocating for a comprehensive approach, the study recommends providing schools with 3R bins and training, sustainable behavior modeling by teachers, alignment of municipal waste collection with school efforts, family reinforcement of waste practices, and curricular integration of waste management. This coordinated approach seeks to bridge the attitude-behavior gap and promote sustainable waste practices across school communities in Tangerang City.